2017
DOI: 10.5535/arm.2017.41.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aquatic Treadmill Training on Gait Symmetry and Balance in Subacute Stroke Patients

Abstract: ObjectiveTo determine the efficacy of aquatic treadmill training (ATT) as a new modality for stroke rehabilitation, by assessing changes in gait symmetry, balance function, and subjective balance confidence for the paretic and non-paretic leg in stroke patients.MethodsTwenty-one subacute stroke patients participated in 15 intervention sessions of aquatic treadmill training. The Comfortable 10-Meter Walk Test (CWT), spatiotemporal gait parameters, Berg Balance Scale (BBS), and Activities-specific Balance Confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…23 A single-participant study of 21 subacute stroke patients using an aquatic treadmill over 15 sessions found improvement in Berg Balance Scale (BBS) scores, a 10-m walk test, and balance confidence when compared to pretest baseline. 24 In a 2018 randomized study in a cohort of 20 subacute stroke patients following a 30-minute 6-week five-times per week comparison assessing land-based aerobic exercise with aquatic treadmill exercise, investigators found the aquatic group showed greater gains in 6-minute-walk test, peak O 2 uptake, and in an endurance exercise measure. 25 A number of these and other studies have assessed balance using BBS scores but finding only comparable improvement to land-exercised control groups with no statistically significant advantage to aquatic programs, although gains were found on both cohorts.…”
Section: Aquatic Immersion and Exercise Effects On The Central Nervoumentioning
confidence: 99%
“…23 A single-participant study of 21 subacute stroke patients using an aquatic treadmill over 15 sessions found improvement in Berg Balance Scale (BBS) scores, a 10-m walk test, and balance confidence when compared to pretest baseline. 24 In a 2018 randomized study in a cohort of 20 subacute stroke patients following a 30-minute 6-week five-times per week comparison assessing land-based aerobic exercise with aquatic treadmill exercise, investigators found the aquatic group showed greater gains in 6-minute-walk test, peak O 2 uptake, and in an endurance exercise measure. 25 A number of these and other studies have assessed balance using BBS scores but finding only comparable improvement to land-exercised control groups with no statistically significant advantage to aquatic programs, although gains were found on both cohorts.…”
Section: Aquatic Immersion and Exercise Effects On The Central Nervoumentioning
confidence: 99%
“…Many studies have demonstrated that physical activity prevents the risk of falls, by increasing strength in the lower limb muscles and improving gait pattern, as well as balance and coordination parameters [ 5 , 6 , 7 , 8 ]. A comprehensive assessment of postural control and balance (both static and dynamic) is recommended in order to design an appropriate and personalized exercise program for fall prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The current evidence includes several studies that support the use of aquatic therapy for the improvement of gait in adults with neurological illnesses [ 6 , 7 , 8 ], however, there are few studies focused on the reeducation of balance using different types of aquatic therapy. Furthermore, there is a lack of studies specifically on these therapies in adults with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing the effects on postural balance performance of the same physical exercises carried out in land and water condition are few and contradictory. Moreover, they investigated only the effect of walking training protocols in unhealthy subjects as stroke patients (Park et al, 2014 ; Lee et al, 2017 ). Only one study involved healthy subjects and demonstrated that a 30-min underwater walking, five times per week for 4 weeks, significantly improved the ML and the AP balance indexes (Lee and Kim, 2017 ).…”
Section: Introductionmentioning
confidence: 99%